Short-chain fatty acids as potential regulators of skeletal muscle metabolism and function - Frampton,J; Murphy,KG; Frost,G; Chambers,ES (Nature Metabolism, 2020)
A key metabolic activity of the gut microbiota is the fermentation of non-digestible carbohydrate, which generates short-chain fatty acids (SCFAs) as the principal end products. SCFAs are absorbed from the gut lumen and modulate host metabolic responses at different organ sites. Evidence suggests that these organ sites include skeletal muscle, the largest organ in humans, which plays a pivotal role in whole-body energy metabolism. In this Review, we evaluate the evidence indicating that SCFAs mediate metabolic cross-talk between the gut microbiota and skeletal muscle. We discuss the effects of three primary SCFAs (acetate, propionate and butyrate) on lipid, carbohydrate and protein metabolism in skeletal muscle, and we consider the potential mechanisms involved. Furthermore, we highlight the emerging roles of these gut-derived metabolites in skeletal muscle function and exercise capacity, present limitations in current knowledge and provide suggestions for future work.